ANALISIS HAMBATAN BELAJAR SISWA PADA MATERI PENGUKURAN PANJANG DI KELAS II SEKOLAH DASAR - I Wayan Arya Suta Ardyansa; Ni Luh Nitiasih; I Ketut Tresna Yasa; I Made Sujana Adnyana (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the learning obstacles experienced by second-grade elementary school students in the topic of length measurement. The learning obstacles include conceptual, procedural, and didactical barriers that affect students’ understanding of measurement concepts, both using standard and non-standard units. This research employed a qualitative descriptive method with second-grade students from an elementary school as the subjects. Data were collected through observation, interviews, and analysis of students’ work.The results indicate that conceptual obstacles occur when students do not yet understand the meaning of length as a measurable quantity and have difficulty distinguishing between standard and non-standard units. Procedural obstacles are reflected in students’ errors when using measuring tools, such as rulers, particularly in determining the starting point and reading measurement results. In addition, students experience difficulties in converting simple units of length, such as from centimeters to meters, and tend to lack accuracy during the measurement process. Meanwhile, didactical obstacles are caused by limited variation in teaching methods and the minimal use of concrete learning media that support students’ understanding.These findings suggest that learning activities on length measurement should be designed in a contextual and activity-based manner to help students construct their understanding gradually. Teachers are encouraged to apply approaches that involve direct exploration, such as measuring objects in students’ surroundings, and to provide appropriate scaffolding. Furthermore, the use of manipulative media, contextual worksheets, and problem-based learning can serve as alternative strategies to enhance student engagement. Thus, learning obstacles can be minimized, and students’ understanding of length measurement concepts can be improved optimally and sustainably.